To find the solutions of the system, we can set y = y and solve for x:
x^2 - 3x + 2 = 2x + 2
Rearranging the equation, we get:
x^2 - 5x + 0 = 0
Factoring the quadratic equation:
x(x - 5) = 0
Setting each factor to 0:
x = 0 or x = 5
Now substituting each value of x back into the second equation y = 2x + 2, we get:
If x = 0,
y = 2(0) + 2
y = 2
So, one solution is (0, 2).
If x = 5,
y = 2(5) + 2
y = 10 + 2
y = 12
So, the other solution is (5, 12).
Therefore, the solutions of the system are (0, 2) and (5, 12).
Find the solutions of the system:
y = x^2 - 3x + 2
Y=2x + 2
(1 point)
Responses

(0,1) and (6,4)
(0,1) and (6,4)

(0,2) and (0,-2)
(0,2) and (0,-2)

(1,0) and (4,6)
(1,0) and (4,6)

No Solution
No Solution
1 answer